Emeraldalicious eaudiobook - Kann, Victoria (Pinkalicious., 2013)
Everyone's favorite pink-loving gal returns in Emeraldalicious, the imaginative, glitterlicious sequel to the #1 New York Times bestselling Pinkalicious! Pinkalicious combines magic, love, and imagination to turn an ordinary place into an Emeraldalicious world. Pinkalicious and Peter visit their favorite park, but on the way Pinkalicious's wand breaks. She isn't worried at all, because she knows just what to do. She takes a stick, some vines, and a very special flower to make a magical wand. When Pinkalicious and Peter finally arrive at the park it's covered in stinky trash! But never fear, Pinkalicious is here with her magical wand, lots of love, and pinktastic rhymes to turn the trash into an Emeraldalicious paradise.